Photoluminescence study of reddish orange emitting Eu3+ activated LaPO4 Nanoparticles via hydrothermal method. Issue 1 (1st October 2022) - Chandran, Aswathy R; Jacob, Linju Ann; Paul, Issac; Jose, Gijo
Abstract : Lanthanum phosphate (LaPO4 ) belongs to the family of rare earth phosphates characterized as a fluorescence material. Europium ion is known for its orange –red fluorescence. In order to include orange –red fluorescence for pure white light generation we are doping LaPO4 with Eu 3+ . The crystalline planes are identified from the XRD pattern show that the particles have monoclinic structure with pure LaPO4 . The addition of sodium ions to the LaPO4 : Eu 3+ sample it is found that the luminescence property gets increased. It is also found that reversal of the emission spectrum intensity takes place for the sodium doped sample which indicates that Eu 3+ ions are located in a highly symmetric environment.